Celery Plant Growth Response Given Organic Fertilizer with Banana Peel and Coconut Water - Alibasyah, Lestari MP; Ningsi, Ririn Apriani; Nurfadila A, Nurfadila A; Trianto, Manap (Jurnal Biologi Tropis, 2024)
Celery (Apium graveolens L.) is a vegetable that has many health benefits because it contains nutrients and antioxidants that makes it popular among the public, but its production is relatively low. One way to improve the quality and quantity of celery plants is to provide liquid organic fertilizer (LOF) of banana peel and coconut water which contains essential nutrients such as calcium, phosphorus, nitrogen, potassium, magnesium, sodium, sulfur, sugar, protein, and two hormones. namely cytokinins and auxins which are needed in the growth of the plant. The study aims to analyze the growth response of celery plants given liquid organic fertilizer (LOF) from banana peel and coconut water. The type of research is an experiment with a complete randomized design (CRD) consisting of 7 treatments, namely (P0 = Control, P1 = 10% banana peel, P2 = 15% banana peel, P3 = 20% banana peel, P4 = 10% coconut water, P5 = 15% coconut water, and P6 = 20% coconut water), each treatment is repeated 6 times with a total sample of 42. The observed variables were plant height, number of leaves, and number of tillers measured at 6 WAP, 8 WAP, 10 WAP, and 12 WAP. Data analysis used ANOVA followed by a 5% significant BNT test with the help of the SPPS 25 program. The results of the research showed that the best growth was at the age of 12 WAP with a concentration of 20% organic fertilizer and banana waste organic fertilizer was more effective than coconut water in increasing the response of celery plant growth.